Knowledge of behavioral risk factors for type 2 diabetes mellitus and its associated factors among women of reproductive age - Tinsae Seyoum; Selamnesh Tesfaye; Yohannes Shiferaw; Rahel Hailu; Dagim Tefera; Zeleke Gebru (PLoS ONE, 2025)
Background Type 2 diabetes accounts for over 90% of all diabetes cases and is caused by a combination of behavioral risk factors. It is currently a serious health issue, particularly among women of reproductive age, as it is associated with reproductive disorders. Preventing it requires knowledge, but there is limited data on behavioral risk factors in Ethiopia. Objective To assess knowledge of the behavioral risks of type 2 diabetes mellitus and its associated factors among women of reproductive age. Methods A community-based cross-sectional study was conducted, with all women in the town serving as the source population. A multistage sampling method was utilized to recruit kebeles, and a systematic random technique was employed to select households at every 13th interval. We completed interview questionnaires for 623 samples. The crude odds ratio was calculated using a bivariate logistic model, and multivariate analysis was performed to control for confounding and identify associated factors among model-fitting variables using an adjusted odds ratio (AOR). Result The knowledge of behavioral risk factors (BRF) among women of reproductive age (WRA) is 47.0% [95% CI, 43.5–50.9], and significant associations were found with the following factors: average family income of between 3000 and 5000 Ethiopian Birr(ETH) 1.81 [95% CI, 1.03–3.18], > = 5001 ETH 1.93 [95% CI, 1.02–3.68], diabetes mellitus (DM) in the friend or relatives 4.03 [95% CI, 1.56–10.46], family history of DM 9.47 [95% CI, 4.74–18.90], source of information: health workers 1.87 [95% CI, 1.04–3.34] and friend or relatives 1.65 [95% CI, 1.04–2.62]. Conclusion Knowledge of behavioral risk factors for type 2 diabetes was poor among study participants. Factors such as family income, diabetes mellitus (DM) in friends or relatives, family history of DM, and sources of information were strongly associated with good knowledge. It is essential to emphasize health education about behavioral risk factors for women.